Efecto comparativo de aceite esencial y extracto acuoso de hojas de Schinus molle L. “molle” sobre el crecimiento de Botrytis cinerea. - Espinoza Pantigozo, Ivonne Kelly (2016)
Botrytis cinerea, phytopathogenic fungus causal agent of gray mold. It is generally controlled by agrochemicals, resulting in serious ecological consequences, so it requires new alternatives for its control, such as the use of plant bioproductos with antimicrobial activity. The aim of this study was to determine the comparative effect of essential oil and aqueous extract of leaves of Schinus molle “molle” on the growth of B. cinerea. The leaves of S. molle were collected of the town of Conache (Laredo); which were dried under shade for 48 hours at room temperature in the laboratory of Phytopathology, and then were crushed to powder. The essential oil was obtained by distillation method for towing water vapor, and the 10% aqueous extract was made; from which the treatments were applied: 0%, 3%, 7%, 15%, using potato dextrose agar medium (PDA) with five sampling units. The media inoculated with B. cinerea for Core needle were placed at (23°C ± 2°C), subsequently evaluated daily the halo of mycelial growth; and at 10 days, the comparative effect of essential oil and aqueous extract of leaves of S. molle was higher in the treatment of 15%, with a greater percentage inhibition of 91.0% and less than 71.0%, with average diameter of growth of 7.4 mm and growth 24.8 mm, respectively for each plant extract. It is concluded that the essential oil of S. molle generates greater effect compared to aqueous extract on the growth of B. cinerea. Keywords: Effect, Schinus molle, Essential oil, Aqueous extract, Botrytis cinerea.